Debating Lapita Distribution, Chronology, Society and Subsistence - Bedford, Stuart; Spriggs, Matthew (Terra Australis, 2019)
This volume comprises 23 chapters that focus on the archaeology of Lapita, a cultural horizon associated with the founding populations who first colonised much of the south west Pacific some 3000 years ago. The Lapita culture has been most clearly defined by its distinctive dentate-stamped decorated pottery and the design system represented on it and on further incised pots. Modern research now encompasses a whole range of aspects associated with Lapita and this is reflected in this volume. The broad overlapping themes of the volume-Lapita distribution and chronology, society and subsistence-relate to research questions that have long been debated in relation to Lapita.